The Effect of Hedonic Shopping Motivation, Shopping Lifestyle And Fashion Involvement With Impulse Buying - Satria Tirtayasa; Myisha Nevianda; Hery Syahrial (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2020)
The purpose of this research is to analyse the direct Effect of Hedonic Shopping Motivation, Shopping Lifestyle and Fashion Involvement with Impulse Buying. The population of this research is Zalora's customer in Medann are unknown, The sample size 96 respondents with using Bernoulli formula sample sise measurement. Meanwhile, the respondents have criteria, such as: respondent expenditure more than Rp 1.500.000,-, ever bought on Zalora more than three time, and the counsumer are the active internet user in Medan(purposive sampling). Data collection was used the Google form questionnaire and the data analysis method is used associative statistical analysis and Partial-Least Square analysis (SEM-PLS). The results of the research showed that the Hedonic Shopping Motivation variable had significant effect with Impulse Buying, the Shopping Lifestyle variable has significant effect with Impulse Buying and the Involvement Fashion variable has significant effect with Impulse Buying.